Engagement with LGBTQ community moderates the association between victimization and substance use among a cohort of sexual and gender minority individuals assigned female at birth. (August 2020) - Phillips II, Gregory; Felt, Dylan; McCuskey, David J.; Marro, Rachel; Broschart, Jacob; Newcomb, Michael E.; Whitton, Sarah W.
Highlights: We test moderators of substance use in LGBT individuals assigned female at birth. LGBT community engagement moderated a victimization - substance use association. We found that outness played a key role in the relationships observed. Abstract: Background: Research has documented higher levels of substance use among sexual and gender minority (SGM) individuals – particularly sexual minority women (SMW) and transgender people – than among their heterosexual and cisgender peers. Because SGM substance use is linked to stigma-based victimization, it is crucial to identify social contexts that may buffer the association between victimization and substance use among SGM. Methods: We explored how engagement with LGBTQ-specific community influences victimization experiences and substance use among 488 SGM individuals assigned female at birth (FAB-SGM; ages 16–32; 26% White) in a large Midwestern city. We tested whether participants who used LGBTQ community spaces differed from those who do not in levels of victimization and substance use, and whether use of LGBTQ spaces buffered SGM from the negative effects of victimization on substance use. Results: Results demonstrated significant associations between victimization and alcohol and use of specific drugs. Contrary to expectations, participants who used LGBTQ spaces reported more victimization and more use of certain substances; however, when controlling for being out about non-heterosexual identity, this association remained only for LGBTQ community centers and school groups. Evidence was mixed for community engagement as a moderator of the association between victimization and substance use. Conclusions: Overall, results indicated that LGBTQ spaces may be associated with adaptive and maladaptive coping functions and should be considered a potential target for health interventions. Findings emphasize the need for increased research on FAB-SGM, including SMW and transgender individuals, and provide actionable recommendations to reduce incidence of victimization and substance use.